The Hanafi School of Islamic Jurisprudence Literature: A Historical Account - Suud Sarim Karimullah,; Arif Sugitanata, (Journal of Islamic History and Manuscript, 2023)
This article focuses on one of the founding figures of the Sunni school of Islamic jurisprudence who contributed to the development of Islamic law, Abu Hanifah. Studying Abu Hanifahs literature can better understand his thoughts and views on Islamic legal issues. It can also provide greater insight into the history of Islamic thought and how Abu Hanifahs thoughts impact Muslim society today. This study uses the heuristic method with critical literature analysis because the data is obtained from various books, journals, and other documentation relevant to the historical approach. The results of this study state that the Hanafi school of Islamic jurisprudence is one of the famous schools of Islamic jurisprudence in the scientific discipline of Islamic law founded by Abu Hanifah. His background and education strongly influence Abu Hanifahs thinking pattern in determining the law. It is also inseparable from the socio-cultural dimension and the politics that underlie the Hanafi school of Islamic jurisprudence, which is seen as a factor affecting Islamic laws rational character. Literature on studying Islamic law in the Hanafi school of Islamic jurisprudence is widely found and spread worldwide. The school of Islamic jurisprudence is even adopted by one-third of the worlds Muslim population. However, remember that some of Abu Hanifahs written works may no longer be available or incomplete. Over time, some manuscripts may be damaged or lost.